The Effect of Brand Thrust on Financial Performance of Property Companies in Indonesia Capital Market - Anastasia, Njo; Sari, Dewi Pricilia (Jurnal Aplikasi Bisnis dan Manajemen, 2020)
The rapid economic growth and development encourage companies to have sustainable competitive advantage in order to compete in the market. One of the strategies to face this competition is building a good brand image. Brand has always been an important factor in company’s growth. The concept of brand thrust was used to show the level of company allocation to enhance their brand image. This study aims to examine the effect of brand thrust on financial performance of property companies in Indonesia capital market for the period 2009-2016. The independent variables used are brand thrust and firm characteristics. The dependent variable used is financial performance. The method used is panel data Ordinary Least Square (OLS) regression with the number of sample are 28 firms of property sector. This study reveals brand thrust, long term debt to assets ratio, stock market beta, market share, operating profit margins, and capital expenditure to property, plant, and equipment have a significant influence on financial performance of property companies.Keywords: brand thrust, firm characteristics, financial performance, property sector, OLS